This article proposes a reflection on the problem of psychiatric training taking into consideration the current situation present in Italy where, apart from public (university) schools of specialization, there are a number of private post-graduate schools - Vari, Autori (Il sogno della farfalla, 2019)
This article proposes a reflection on the problem of psychiatric training taking into consideration the current situation present in Italy where, apart from public (university) schools of specialization, there are a number of private post-graduate schools which qualify one to practice the profession of psychotherapist. By keeping separate the more didactic-educational aspect from the training, there is an attempt to verify how much attention is devoted to the latter because within the university schools more and more students ask for a possibility to discuss clinical cases and understand the sense of a therapeutic relationship. Furthermore, it is necessary to verify, not only the didactical learning of students, but also their personal aptitudes during the four years of specialization. There seems to be an incongruity between the statutes that govern the single private specialization schools that regulate the supervision of clinical cases and in some cases prescribe an obligatory didactic analysis for the student, and what happens in a university context.